Market Power in an Emerging Economy: Evidence from South African Listed Nonfinancial Firms - Ingrid Woolard; Fiona Tregenna; Reena das Nair; Lawrence Edwards (Journal of Economics Business Industry, 2024)
This study examines market power dynamics in South Africa, an emerging market and developing economy, by estimating firm-level markups for listed nonfinancial corporations and assessing their variation across time, sectors, firm size, profitability, and macroeconomic conditions. Design Using annual financial statement data for 215 Johannesburg Stock Exchange-listed nonfinancial firms across 16 sectors from 2004 to 2022, the study applies a production-based markup estimation method following De Loecker and Warzynski. Sales-weighted aggregate markups, sectoral distribution analysis, and fixed-effects panel regressions are used to evaluate markup movements and their relationship with firm performance and macroeconomic variables. The results show an average aggregate markup of 1.78, indicating market power, but no consistent upward trend as commonly observed in advanced economies. South African markups are volatile, rising during the commodity boom, declining during the global financial crisis and COVID-19 shock, and recovering by 2022. High markups are concentrated among large firms and in technology, real estate, and telecommunications, while transportation, oil and gas, and retail record lower markups. Markups are positively associated with profitability but negatively associated with interest rates and exchange rate depreciation. The study provides novel firm-level evidence on market power in an underexplored emerging economy and shows that markup dynamics in such contexts are shaped strongly by macroeconomic instability and commodity cycles. Policymakers should target dominant firms and high-markup sectors through stronger competition enforcement. The study is limited to listed firms; future research should include unlisted firms and causal macroeconomic modelling.